2000
DOI: 10.1007/s001340051197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of respiratory variables on mortality in non-ARDS and ARDS patients requiring mechanical ventilation

Abstract: No independent significant association was seen between 90-day mortality and degree of hypoxaemia, PEEP, MAP or BE for the first full week of ICU care in either ARDS or non-ARDS. In a sub-group of non-ARDS a lower PaO2/FIO2 and MAP tended to influence mortality where a significant association was seen for 3 of 7 study days. Age, gender, APS, presence of a chronic disease and a pulmonary/non-pulmonary reason for the respiratory failure were associated with mortality in non-ARDS, while only age and APS showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
5
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 19 publications
4
48
5
3
Order By: Relevance
“…The value of pH in our study was higher than that reported in the studies by Brun-Buisson and Villar (7.35 vs. 7.30), and the difference may due to the inconsistence in patients selection (42,43). Controversies lies in the association between PaO 2 /FiO 2 at the onset of ARDS and the adverse outcomes in ARDS (42)(43)(44)(45), but our study revealed that initial PaO 2 /FiO 2 is not an independent predictor of mortality, which we suspected was attributed to the insignificant difference in PEEP because PaO 2 /FiO 2 has been reported to vary depending on ventilator strategy and is sensitive to ventilator settings (46), and early change of PaO 2 /FiO 2 being too likely to be associated with outcomes in ARDS (10,47).…”
Section: Discussionmentioning
confidence: 99%
“…The value of pH in our study was higher than that reported in the studies by Brun-Buisson and Villar (7.35 vs. 7.30), and the difference may due to the inconsistence in patients selection (42,43). Controversies lies in the association between PaO 2 /FiO 2 at the onset of ARDS and the adverse outcomes in ARDS (42)(43)(44)(45), but our study revealed that initial PaO 2 /FiO 2 is not an independent predictor of mortality, which we suspected was attributed to the insignificant difference in PEEP because PaO 2 /FiO 2 has been reported to vary depending on ventilator strategy and is sensitive to ventilator settings (46), and early change of PaO 2 /FiO 2 being too likely to be associated with outcomes in ARDS (10,47).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with adult respiratory distress syndrome older age is clearly associated with higher mortality rates. 87,88 Similar data specific to mechanical ventilation made necessary by postoperative pulmonary complications are not available. Ely et al 89 prospectively studied whether age represents an independent effect on the outcomes of patients requiring mechanical ventilation after admission to an intensive care unit.…”
Section: Non-invasive Ventilationmentioning
confidence: 99%
“…It is therefore important to improve respiratory care of these patients [11,25,95,96]. Animal studies play an important part in expanding our knowledge in this research area, leading to better clinical routines to minimize the risks associated with mechanical ventilation.…”
Section: Ethical Issuesmentioning
confidence: 99%